Heart failure: mechanistic insights and precision therapeutic strategies - Zhang, Fang; Zhang, Xiang; Jian, Jing; Zeng, Xu; Zheng, Chao; Zhang, Yaxi; Gao, Jinquan (Frontiers in Cardiovascular Medicine, 2025)
Heart failure (HF) is a major global health problem associated with high illness rates, mortality, and healthcare costs. Although advances in diagnosis and therapy have improved outcomes for some patients, effective treatment—especially for HF with preserved ejection fraction (HFpEF)—remains limited. HF develops through complex interactions among neurohormonal activation, metabolic remodeling, mitochondrial dysfunction, inflammation, fibrosis, and microvascular impairment. Recent discoveries in these areas have revealed new molecular and cellular targets that may lead to more precise therapies. Novel pharmacological agents, metabolic modulators, device-based interventions, and regenerative approaches are reshaping the treatment landscape. In addition, personalized strategies such as multi-omics profiling, biomarker-guided management, and artificial intelligence–assisted diagnosis hold promise for better risk prediction and individualized care. However, translating mechanistic discoveries into clinical benefit remains a challenge. Future research integrating molecular insights with clinical phenotyping will be essential to achieve precision treatment and improved outcomes in patients with HF.